The impact of power on reliance on feelings versus reasons in decision making - HUANG, Yunhui (Institutional Knowledge at Singapore Management University, 2015)
We examine the impact of power on consumer decision making. Results from four experiments provide converging evidence that people in high- (low-) power states are more likely to rely on affective feelings (cognitive reasoning) in making judgments and decisions.